2022
DOI: 10.21608/tsnj.2022.236057
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Workplace Ostracism and Organizational Cynicism on Organizational Silence among Nursing Staff

Abstract: Background: Workplace ostracism limits opportunities for social interaction and discourages nursing staff from forming lasting and meaningful relationships in an organization and organizational cynicism and organizational silence are barriers against the improvement of organizations. Aim: The study aimed to investigate the effect of workplace ostracism and organizational cynicism on organizational silence among nursing staff. Subjects and Method: Design: Descriptive correlation research design was utilized. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A study conducted among healthcare professionals in Egypt assessed the mental health consequences and reported anxiety (42.6%), depression (59.0%), and insomnia (51.9%) (12). According to a study done by Elhanafy (13) founded that the prevalence of workplace ostracism was 52.26%, while 45.9 % of the nursing staff had high level of organizational silence. Also, found that more than half of staff nurses (53%) had a high level of organizational silence (7).…”
Section: Significance Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted among healthcare professionals in Egypt assessed the mental health consequences and reported anxiety (42.6%), depression (59.0%), and insomnia (51.9%) (12). According to a study done by Elhanafy (13) founded that the prevalence of workplace ostracism was 52.26%, while 45.9 % of the nursing staff had high level of organizational silence. Also, found that more than half of staff nurses (53%) had a high level of organizational silence (7).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…In contrast to the current findings, the results of Elhanafy and Ebrahim ., (2022) (13) revealed that More than ninety percent (92.5%) of nursing staff have a low level of workplace ostracism.…”
Section: Concerning Level Of Psychological Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…The healthcare industry is strongly people‐oriented, and healthcare work is often done in teams. Hospitals are social environments and offer a good opportunity to interact and communicate with colleagues and patients (Elhanafy & Ebrahim, 2022). However, workplace ostracism undermines this interaction (Robinson et al., 2013).…”
Section: Introductionmentioning
confidence: 99%